Neoplastic transformation by a cloned human cytomegalovirus DNA fragment uniquely homologous to one of the transforming regions of herpes simplex virus type 2. - Clanton, D J (1983)
Specific DNA fragments of human cytomegalovirus strain Towne exhibited sequence homology to the transforming regions of herpes simplex virus type 2 (HSV-2) when examined by nitrocellulose filter hybridization under nonstringent conditions. Cloned Towne Xba I fragments B and C were homologous to both Bgl II transforming fragments N and C of HSV-2 DNA, whereas cloned Towne Xba I fragment E was uniquely homologous to HSV-2 Bgl II fragment C. Furthermore, Towne Xba I fragment E exhibited homology to a unique fragment of cytomegalovirus strain AD169 but lacked homology to the recently identified Xba I transforming (focus-forming) fragment N. Normal diploid Syrian hamster embryo cells transfected with cloned Towne Xba I fragment E displayed colonies of refractile, rapidly dividing cells which escaped senescence to form immortal cell lines. At early passages, these lines exhibited growth in 2% serum and formed small (less than 0.1 mm) colonies in 0.3% agarose. Serial passaging resulted in the appearance of large (greater than 0.25 mm) colonies in agarose, indicating the involvement of more than one step in Towne Xba I fragment E-induced transformation of the diploid hamster embryo cells. NIH 3T3 cells transfected with Towne Xba I fragment E rapidly displayed large colonies in agarose and tumors in vivo.